Fiscalidad y café mexicano. El porfiriato y sus estrategias de fomento económico para la producción y comercialización del grano (1870-1910) - Rodríguez Centeno, Mabel M. (El Colegio de México, A.C., 2004)
The author analyzes how Mexican liberal policies for economic development combined with international markets in the late-Nineteenth century.  It focuses on the case of coffee because it clearly  shows  that  the  grower's main incentive  were  the high prices of this product in international markets. The analysis centers on the specific cases of Michoacan, Jalisco, Colima, Oaxaca, Chiapas  and Veracruz,  emphasizing  the central  role of federal and state government  support for expanding coffee production, through fiscal incentives and the development of transportation means.